'Lessons Learned' from introducing universal strategies designed to support the motor and functional skills of Reception and Year 1 children in a sample of primary schools in South East England. Issue 1 (2nd January 2017) - Hutton, Eve; Soan, Sue
Abstract : This article describes an evaluation of universal resources designed to support motor development in Reception and Year 1 children. Four schools (Year R–Year 6) in the South East of England, three with high numbers of disadvantaged children participated. Senior leadership influenced take up of the initiative. Health and well-being practitioners and occupational therapy students contributed to 'roll out' of the resources with support provided by the authors over 12 weeks. Interview and focus group data from participating staff were gathered alongside examples of schoolwork from pupils. School staff needed access to support when incorporating universal strategies. The initiative contributed to schools working towards Healthy Schools targets. At the end of 12 weeks, improvements in children's sitting position, handwriting and lunchtime skills were noted, warranting further exploration of this approach to address the needs of children with poor motor skills at school entry.